2009
DOI: 10.2320/matertrans.mra2008370
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Notch Properties of Heat-Treated Ti-4.5Al-3V-2Mo-2Fe Laser Welds

Abstract: The microstructure and transformation behavior of Ti-4.5Al-3V-2Mo-2Fe alloy and its laser welds after various heat treatments were investigated. Notch properties, such as impact toughness and notched tensile strength, were also measured on the welds to choose an appropriate post-weld heat treatment (PWHT) of the alloy. The temperature regimes in which transformed into 0 , 00 or retained as after quenching were identified and discussed. The results indicated that 00 could be obtained primarily by rapid quenchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…At Institute of Aerospace and Astronautical Science (ISAS/JAXA), spherical fuel and gas tanks have been fabricated by superplastic blow forming of titanium alloy sheets and have been used for several man-made satellites [3]. It has been reported that SP-700 exhibits martensitic transformation upon quenching from high temperature [1,2,4]. Chung et al [4] conducted transmission electron microscope (TEM) observation and claimed that two kinds of martensite phases exist in SP-700, namely with the hexagonal-closepacked (hcp) crystal structure and with an orthorhombic structure.…”
Section: Introductionmentioning
confidence: 99%
“…At Institute of Aerospace and Astronautical Science (ISAS/JAXA), spherical fuel and gas tanks have been fabricated by superplastic blow forming of titanium alloy sheets and have been used for several man-made satellites [3]. It has been reported that SP-700 exhibits martensitic transformation upon quenching from high temperature [1,2,4]. Chung et al [4] conducted transmission electron microscope (TEM) observation and claimed that two kinds of martensite phases exist in SP-700, namely with the hexagonal-closepacked (hcp) crystal structure and with an orthorhombic structure.…”
Section: Introductionmentioning
confidence: 99%
“…1, 17) were used to determine the NTS values of the aged specimens. The use of such configuration could completely reflect notch brittleness of the tested specimens under tensile loading.…”
Section: +1mentioning
confidence: 99%
“…The use of such configuration could completely reflect notch brittleness of the tested specimens under tensile loading. [16][17][18]20) For the welds, the notches were located at the center of the fusion zone (FZ) to ensure the crack growth along the weld centerline during tensile loading. Notched tensile tests were carried out in air at a constant displacement rate of 1.0 mm/ min.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%